Management of Stress through Philosophical Reflections: Teachings by Boethius (d. 524) for Our Modern Life - Classen, Albrecht (Conatus - Journal of Philosophy, 2022)
While many scholars in the medical and psychological profession offer specific suggestions about how to handle stress and to overcome its negative impact, very few have ever considered philosophical reflections as a critical tool for this problem. One of the greatest moments of stress would certainly be when an individual has to face his/her death penalty and subsequent execution, especially if s/he feels innocent. Already ca. 1.500 years ago, the late antique philosopher Boethius (d. ca. 524) had to answer for himself how to cope with this situation, being imprisoned and waiting for his last terrible moment. When he composed his treatise, The Consolation of Philosophy, he created one of the most influential philosophical reflections on life’s burning issues. This treatise continues to offer fundamental insights into how to come to terms with the conflicts and stresses of human existence, and it is discussed here as a profoundly philosophical answer to stress in universal terms.